Competências essenciais necessárias à atuação dos bibliotecários gestores de pessoas nas Bibliotecas da Rede Federal de Educação Profissional, Científica e Tecnológica - Mendes, Aline Rodrigues de Lima (2014)
The research aimed to identify the core competences of people managers librarians in the libraries of the Federal Network of Vocational Science and Technology, seeking to answer the following question: what are the core competences that librarians need to have to take on the role as manager of people in the libraries of EPCT Network? Aims to identify, in the view of librarians, managers, key competences for his performance in people management in the libraries of the Federal Network of Vocational Education, Science and Technology. To this end, we sought theoretical foundation in skills, core competences, people management and academic libraries. Research as to the objectives was classified as exploratory, with qualitative and quantitative approach, with data collection done by semi-structured questions (open and closed). For the environment, it is classified as a field, and the method of support of the analyzes is based on structuralist approach. The data collection instrument used was the electronic questionnaire prepared and sent through Google Docs tool. The research involved the participation of 42 librarians from various regions of Brazil, which sets up 9.56% of the total universe of research, which is 439 librarians throughout the country Data analysis and discussion of the results showed that the core competences necessary to support the practices of people management by librarians in the libraries of EPCT Network, pointed out by these professionals are: People Management, Leadership, Teamwork, Making librarianship (practices Librarian), Communication, Interpersonal Relationship, Responsibility, Vision holistic and Commitment. It was also the latent fact that most of these professionals are expert female and the management is on average 2-5 years (35%), and that most of them had experience of people management before joining Network EPCT. The skills they believe they are responsible as personal characteristic, leadership skills and technique as he thinks he has the role as a manager of people, was to respond to the demands and requests. Managerial skills that librarians apply to the exercise of employee management were, among others: know how to communicate, take responsibility, engage and be committed to the role.